Likuiditas, Solvabilitas, Kinerja Keuangan, dan Pertumbuhan Penjualan terhadap Struktur Modal pada Perusahaan Manufaktur yang Terdaftar di BEI Tahun 2016-2020 - Naomi Octavia Sibuea; Nico Alexander (Journal of Management and Bussines (JOMB), 2022)
This study aims to explain the effect of liquidity, solvency, financial performance, and sales growth on the capital structure. This research method is descriptive quantitative. The population of this study were 181 manufacturing companies and only 48 met the criteria using the purposive sampling technique. This study uses secondary data with classical assumption test and multiple regression analysis. The results showed that the regression equation obtained was Y = 0.581 – 0.028X1 + 0.017X2 + 0.033X3 + 0.288X4 + e. The value of the coefficient of determination (R2) R Square value of 0.155 or equivalent to 15.5%. That is, 15.5% of Capital Structure can be explained and influenced by changes in the independent variable, and the remaining 84.5% is influenced by other variables not used in this study. In conclusion, simultaneously liquidity, solvency, financial performance, and sales growth have a significant and significant effect on the capital structure. Partially, only the Sales Growth variable has a positive and significant effect on the Capital Structure. Meanwhile, Liquidity, Solvency and Financial Performance partially have no effect on the Capital Structure of Manufacturing Companies Listed on the IDX in 2016-2020. Keywords: Financial Performance, Liquidity, Sales Growth, Solvency, Capital Structure